Plunging into a world? - Ingrid Scharlau; Miriam Körber; Andrea Karsten (EARLI, 2019)
Although there is considerable research on and knowledge about students' conceptualizations of learning or academic practices and skills, the variability of these conceptualizations has been consistently neglected. In the present study, we address this variability in the field of academic reading with the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students' conceptual metaphors of reading. Our specific methodological approach to identify the structure of these conceptual metaphors allows to analyze subjective agency on a lexical as well as grammatical level. The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors in a sample of 143 texts written by bachelor students.